Biochar-Based Materials for Water Purification: A Comprehensive Review - Zeena Razaq Katoof; Noor Ulhuda Sabah Hussein; Thaqeef Murtada Jawad; Zeena Razaq Katoof; Noor Ulhuda Sabah Hussein (Universitas Negeri Malang, 2026)
With the rapid industrialization, urbanization and agricultural developments, water pollution has emerged as one of the most critical environmental issues of the world. The traditional water treatment technologies are also costly, inefficient and have secondary pollutants. Biochar is a carbon rich material generated by thermochemical conversion of biomass in the absence of oxygen and has shown promise as a sustainable, economical adsorbent for water purification. The porous structure, high specific surface area, and large number of functional groups on the surface and tunable physicochemical properties make biochar a material that has proven to have very high potential to remove a wide range of contaminants from an aqueous environment. This review summarizes the technologies of biochar production, physicochemical properties and modification methods to improve adsorption performance. The mechanisms involved in pollutant removal, such as electrostatic interaction, ion exchange, filling the pore volume, surface complexation, and π–π interaction are critically discussed. Moreover, the application of pristine and engineered materials of biochar for heavy metal, dye, pharmaceuticals, nutrients and emerging contaminant remediation is systematically reviewed. Current problems with the large scale implementation, regeneration, environmental safety and economic feasibility are also discussed. Finally, future research directions are suggested to help the development of high-performance biochar based materials in sustainable water treatment technologies.